Knowledge, Applicability, and Barriers of Telemedicine in Egypt: A National Survey. (10th June 2021) - Alboraie, Mohamed; Allam, Mahmoud Abdelrashed; Youssef, Naglaa; Abdalgaber, Mohammad; El-Raey, Fathiya; Abdeen, Nermeen; Mahdy, Reem Ezzat; Elshaarawy, Omar; Elgebaly, Ahmed; Haydara, Tamer; Abd-Elsalam, Sherief; Nassar, Yusuf Abdullah; et al.
Abstract : Objectives . The study is aimed at evaluating knowledge, attitude, and barriers to telemedicine among the general population in Egypt. Methods . A questionnaire-based cross-sectional design was carried out among the general Egyptian population. A convenience sampling method was used to approach the eligible participants from University Teaching Hospitals of eight governorates from May to July 2020. Results . A total of 686 participants filled the questionnaire (49.4% were males, mean age 36.7 ± 11.2 years old). Half of the participants stated that they previously used a telemedicine tool, mainly to follow up laboratory results (67.3%). Video or phone calls (39.3%) and mobile applications (23.7%) were the most commonly recognized telemedicine tools by the participants. The included participants exhibited a high level of knowledge and attitude towards telemedicine. On the other hand, 21.9% stated that telemedicine services could jeopardize patient privacy. 32.8% reported that telemedicine service could lead to disclosing medical information to people who are not authorized to do so. Almost half of the participants agreed to strongly agreed that telemedicine service could increase medical errors. 60.80% of the participants said that they are more likely to prefer telemedicine than traditional ways. However, 13.70% stated that telemedicine is more likely to be challenging to use. Conclusion . The Egyptian population has high knowledge about the applications of telemedicine. In addition, the vast majority of Egyptians appear to perceive the benefits of telemedicine positively and are willing to use it. However, some barriers that have been found must be taken into consideration to adopt telemedicine successfully, especially for people who are old, are low educated, and live in remote areas. Future studies should address the utility of telemedicine in improving the quality of healthcare and patient's health outcome and quality of life.